2020
DOI: 10.3390/brainsci10010039
|View full text |Cite
|
Sign up to set email alerts
|

Infants Segment Words from Songs—An EEG Study

Abstract: Children’s songs are omnipresent and highly attractive stimuli in infants’ input. Previous work suggests that infants process linguistic–phonetic information from simplified sung melodies. The present study investigated whether infants learn words from ecologically valid children’s songs. Testing 40 Dutch-learning 10-month-olds in a familiarization-then-test electroencephalography (EEG) paradigm, this study asked whether infants can segment repeated target words embedded in songs during familiarization and sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 22 publications
(41 citation statements)
references
References 116 publications
(251 reference statements)
3
32
0
Order By: Relevance
“…The present results significantly extend previous research on infants' musical grouping abilities by using ecologically valid musical stimuli and by requiring infants to group native song melodies into perceptual chunks while the song unfolds Krumhansl 1990 andNazzi et al, 2000;Hawthorne & Gerken, 2013). This study also extends our knowledge on infants' recognition of phonological units in song lyrics from syllables (François et al, 2017;Lebedeva & Kuhl, 2010;Suppanen et al, 2019;Thiessen & Saffran, 2009), rhymes (Hahn et al, 2018), and single words (Snijders et al, 2020) to larger prosodic units, namely phrases. The potential functional relevance of these findings will be discussed below.…”
Section: Contributionsupporting
confidence: 81%
See 4 more Smart Citations
“…The present results significantly extend previous research on infants' musical grouping abilities by using ecologically valid musical stimuli and by requiring infants to group native song melodies into perceptual chunks while the song unfolds Krumhansl 1990 andNazzi et al, 2000;Hawthorne & Gerken, 2013). This study also extends our knowledge on infants' recognition of phonological units in song lyrics from syllables (François et al, 2017;Lebedeva & Kuhl, 2010;Suppanen et al, 2019;Thiessen & Saffran, 2009), rhymes (Hahn et al, 2018), and single words (Snijders et al, 2020) to larger prosodic units, namely phrases. The potential functional relevance of these findings will be discussed below.…”
Section: Contributionsupporting
confidence: 81%
“…Nevertheless, the current study provided no evidence for easier segmentation in ID song than ID speech. This is contrary to previous studies which reported a song benefit for infants' linguistic processing (François et al, 2017;Lebedeva & Kuhl, 2010;Thiessen & Saffran, 2009), but is in line with other work where no processing benefit for songs was observed (Snijders et al, 2020;Suppanen et al, 2019). In the following, we will discuss possible reasons for the lack of a song advantage in the current study.…”
Section: Contributionsupporting
confidence: 68%
See 3 more Smart Citations